Lessons in art and architecture from the Qur’anic surah al-Shu’ara’ (the Poets) - Omer, Spahic (Penerbit USM, 2019)
This paper discusses the lessons in art and architecture in the Qur’anic chapter, or surah,al-Shu’ara’ (the Poets). The discussion shows that poetry as an art cannot be equated with a divine revelation, nor can poets and their followers with Prophet Muhammad (pbuh) and his followers. Architecture as a noble enterprise is likewise not to be employed as a sign of leading a life of depravity and extravagance in luxury and self-indulgence. Instead, it is to be used for cultivating virtue and for pursuing a greater and more authentic and sustainable good. Poetry and architecture should be developed and dealt with as signs (ayat), testifying to the greatness and benevolence of the Creator and Master of all creation. They are to function as such inspired and guided by the signs of revelation and amidst the innumerable signs of creation. The paper presents the cases of art and architecture as per the content of surah al-Shu’ara’, regarding them as human-made signs.